A SVET study of the inhibitive effects of benzotriazole and cerium chloride solely and combined on an aluminium/copper galvanic coupling model. (September 2016) - Coelho, L.B.; Mouanga, M.; Druart, M.-E.; Recloux, I.; Cossement, D.; Olivier, M.-G.
Highlights: SVET shows the galvanic corrosion for an aluminium/copper model in NaCl solutions. SVET depicts the inhibitive actions of benzotriazole and cerium chloride. Benzotriazole rapidly reacts with copper surfaces, but inhibition is non-persistent. Cerium ions react with the hydroxyl ions, blocking the copper surface after 46 h. A synergistic inhibitive effect is achieved by combining benzotriazole and cerium salt. Abstract: An aluminium/copper galvanic coupling model suitable for Scanning Vibrating Electrode Technique (SVET) analysis was elaborated with the aim of simulating a galvanic couple characteristic of AA 2024. The inhibitive effects brought by benzotriazole (BTA) and cerium chloride (CeCl3 ) on the Al/Cu model were evaluated, separately and combined, in neutral aerated sodium chloride solutions. A positive synergistic effect was revealed yielding permanent corrosion protection for 46 h of immersion. Complementary techniques such as UV spectrophotometry and ToF-SIMS were employed, respectively, to investigate the decomposition of BTA molecules and to confirm the chemical composition of a combined BTA-based/Cerium-based layer.